2018
DOI: 10.1021/acs.bioconjchem.7b00791
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Cysteine Scanning To Identify Stable Antibody Conjugation Sites for Maleimide- and Disulfide-Based Linkers

Abstract: THIOMAB antibody technology utilizes cysteine residues engineered onto an antibody to allow for site-specific conjugation. The technology has enabled the exploration of different attachment sites on the antibody in combination with small molecules, peptides, or proteins to yield antibody conjugates with unique properties. As reported previously ( Shen , B. Q. , et al. ( 2012 ) Nat. Biotechnol. 30 , 184 - 189 ; Pillow , T. H. , et al. ( 2017 ) Chem. Sci. 8 , 366 - 370 ), the specific location of the site of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 37 publications
5
104
0
Order By: Relevance
“…The importance of site-specific TCO conjugation was evident in our data, as seen by differences in both tumor and blood signal between 7C2-TCO 2 and 7C2-TCO 6 , a comparison that was enabled by recent developments in site-specific conjugation technology. 47 In addition to controlling stoichiometry, this technology also provides pharmacokinetic benefits by avoiding the presence of high antibody conjugation ratio species that, in the case of antibody-drug conjugates, has previously led to increased clearance 54 and may be associated with undesirable biodistribution. Relatively similar antibody binding in vitro suggested that the observed increase in tetrazine signal originated from surface-bound tetrazine (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of site-specific TCO conjugation was evident in our data, as seen by differences in both tumor and blood signal between 7C2-TCO 2 and 7C2-TCO 6 , a comparison that was enabled by recent developments in site-specific conjugation technology. 47 In addition to controlling stoichiometry, this technology also provides pharmacokinetic benefits by avoiding the presence of high antibody conjugation ratio species that, in the case of antibody-drug conjugates, has previously led to increased clearance 54 and may be associated with undesirable biodistribution. Relatively similar antibody binding in vitro suggested that the observed increase in tetrazine signal originated from surface-bound tetrazine (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HER2 THIOMAB™ antibodies (clone 7C2) were engineered with cysteine residues at one or more positions 47 (LC:K149C, LC:K149C+HC:L177C or LC:K149C+HC:L177C+HC:Y376C) for conjugation to the click-reactive linker [(4E)-cyclooct-4-en-1-yl] N-[3-[2-[2-[3-[3-(2,5-dioxopyrrol-1-yl)propanoylamino] propoxy]ethoxy]ethoxy]propyl]carbamate (i.e., “TCO-PEG 3 -maleimide”) to give final conjugates with approximately 2, 4, or 6 TCO groups per antibody, respectively. Conjugation was accomplished by first deblocking the THIOMAB™ antibodies followed by conjugation of TCO-PEG 3 -maleimide to the free engineered cysteine residues as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, all of the conjugates were derived from cysteine residues engineered into the LC‐K149 sites of the employed antibodies, and this site‐specific conjugation approach afforded highly homogeneous conjugates with drug‐to‐antibody ratios between 1.9 and 2.0 (Table ). In addition, our prior research indicated that attachment of similar disulfide‐containing linkers to the LC‐K149 antibody site provided conjugates with improved in vivo stability properties relative to ADCs produced using many other possible attachment locations . As a prelude to evaluating the conjugates in animals, we assessed their stabilities in whole blood obtained from various species.…”
Section: Methodsmentioning
confidence: 99%
“…More recent work from Genentech used a scanning approach similar to ours, whereby a cysteine was substituted at every residue in an anti-HER2 IgG1. 28 Once conjugated, these constructs generated a large ADC library that was interrogated in order to identify those with improved stability relative to conventional cysteine conjugates. Then, the team used structural information to evaluate whether solvent accessibility around the conjugation sites contributed to stability; no significant correlation was found between the two features.…”
Section: Discussionmentioning
confidence: 99%